Forced Marriage in Mojorejo Village Indonesia: A Qualitative Study from Islamic Law and Human Rights Perspectives - Ida Rahmawati; Isnatin Ulfa (CV. Dyoqu Publishing and Management, 2026)
Background:Marriage is a social institution that plays a crucial role in forming families and maintaining the continuity of social life. From the perspective of Islamic law and human rights, marriage should ideally be based on the consent and willingness of both parties, without any element of coercion. However, in social practice, cases of forced marriages by parents or guardians of their children are still found. This phenomenon demonstrates a gap between normative legal principles and prevailing social practices. Aims:This study aims to analyze the practice of forced marriage from the perspective of Islamic law and human rights and to examine women's independence in determining their life partner. Methods:This study used a qualitative approach with field research. Data were obtained through interviews and observations with informants involved in forced marriage practices in Mojorejo Village, Kebonsari District, Madiun Regency. Data analysis was conducted using an interactive analysis model that included data reduction, data presentation, and drawing conclusions. Result:Research shows that forced marriages persist due to the influence of strong social, cultural, and family interests within society. In some cases, marriage decisions are largely made by parents or guardians, limiting an individual's freedom to choose a life partner. This situation demonstrates a gap between social practices and the principles of Islamic law and human rights, which emphasize the importance of mutual consent in marriage. Conclusion:This research confirms that the practice of forced marriage is not entirely in line with Islamic law and human rights principles, which uphold individual freedom to choose a life partner. Therefore, public awareness is needed regarding the importance of the consent of both prospective bride and groom in marriage as a form of protection for individual rights and justice in family life.